Issues in operating childcare centers in Malaysia - Nor Azah Abdul Aziz; Nur Hanani Zakaria; Emilda Hashim; Roznim Mohamad Rasli; Erni Marlina Saari; Mazlina Che Mustafa; Sopia Md Yassin (International Journal of Evaluation and Research in Education (IJERE), 2021)
This paper discusses the qualifications of operators of Malaysian childcare centers, namely TASKA and TADIKA, and the challenges faced by practitioners in the industry of early childhood education (PAKK). This research used both qualitative and quantitative methods involving interviews and a survey. The sample study comprised 727 respondents consisting of 282 operators of TASKA and 343 operators of TADIKA. The research used a set of questionnaires and interview guidelines. The findings of the quantitative method showed the operators of TASKA and TADIKA had a diverse range of professional and academic qualifications, while the findings of the qualitative method highlighted a wide spectrum of challenges faced by operators of centers involved in the early childhood education industry. Collectively, such findings suggest that running a childcare center is fraught with a myriad of challenges encompassing economic, logistical, social, educational, and financial factors, which have to be addressed effectively. Certainly, prospective operators must seek assistance from those who are involved in the running, monitoring, and managing of such centers, notably experienced practitioners and relevant government officers. Also, to become successful entrepreneurs in this industry, they need to develop the passion and zeal to operate such centers with great success.